2005
DOI: 10.1177/0361198105191500111
|View full text |Cite
|
Sign up to set email alerts
|

Going South?

Abstract: The recent increase in flight delays in the U.S. domestic system is analyzed by estimating an econometric model of average daily delay that incorporates the effects of arrival queuing, convective weather, terminal weather conditions, seasonal effects, and secular effects (trends in delays not accounted for by other variables). From the estimation results it was possible to quantify some sources of higher delays in late 2003 and early 2004 and track changes in delays that are not attributable to major causal fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In flight‐delay studies, multiple regression analysis is used to predict the average delay (dependent variable). Independent variables could include factors such as arrival queuing, convective weather, terminal weather, clear time holding, flight operations, passenger loads, and demand (Hansen and Hsiao 2005; Hansen and Zhang 2005; Zhang and Nayak 2012). This method requires nonmissing values and has very restricted assumptions including normality, linearity, homoscedasticity, and nonmulticollinearity, since ordinary least squares (OLS) is used for estimating parameters.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In flight‐delay studies, multiple regression analysis is used to predict the average delay (dependent variable). Independent variables could include factors such as arrival queuing, convective weather, terminal weather, clear time holding, flight operations, passenger loads, and demand (Hansen and Hsiao 2005; Hansen and Zhang 2005; Zhang and Nayak 2012). This method requires nonmissing values and has very restricted assumptions including normality, linearity, homoscedasticity, and nonmulticollinearity, since ordinary least squares (OLS) is used for estimating parameters.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In another paper, Abdelghany et al (2004) developed a flight-delay model using the classical, shortest-path algorithm to predict down-line flight delays and alert for crew/aircraft operation breaks occurring due to any operation irregularity. Hansen and Hsiao (2005) constructed an econometric model of average daily delay to estimate delays influenced by factors such as arrival queuing, convective weather, and terminal weather. In addition to these aggregated models, other studies examined flight-delay situations at the individual flight level.…”
Section: Literature Reviewmentioning
confidence: 99%
“…About correlation between delay information system and spatial airport grid distribution, Hansen and Hsiao used the econometric model to examine the daily mean of 32 airports' take-of delays in the United States from a time dimension. Te trend efects, including aircraft queues, fight schedule, and meteorological conditions, are statistically analyzed [12]. Tey found that the increase in total fight and operation demand would aggravate airport delays in the airport grid distribution.…”
Section: Introductionmentioning
confidence: 99%